Enantio‐ and Regioselective Palladium(II)‐Catalyzed Dioxygenation of (Aza‐)Alkenols. (6th September 2021) - Giofrè, Sabrina; Molteni, Letizia; Nava, Donatella; Lo Presti, Leonardo; Beccalli, Egle Maria
Abstract: An oxidative Pd‐catalyzed intra‐intermolecular dioxygenation of (aza‐)alkenols has been reported, with total regioselectivity. To study the stereoselectivity, different chiral ligands as well as different hypervalent‐iodine compounds have been compared. In particular, by using a C‐6 modified pyridinyl‐oxazoline (Pyox) ligand and hypervalent iodine bearing an aromatic ring, an excellent enantio‐ and diastereoselectivity has been achieved. Abstract : A palladium‐catalyzed intramolecular difunctionalization of (aza‐)alkenols with excellent regioselectivity is reported. A new generation of C‐6‐modified Pyox ligands together with the use of unusual hypervalent iodine reagents as oxidants enabled the generation of acyloxy‐functionalized heterocycles in excellent enantio‐ and diastereoselectivity.